Odpowiedzi

  • Użytkownik Zadane
2010-02-23T16:30:04+01:00
1)
2x+8-5x-15=2
-3x=9
x=-3

2)
-2x-6+8x+12=6
6x=0
x=0

3)
3-2x+3x+4=-3+2x+5x+4
-6x=-6
x=1

4)
-x-3+2x-1=1+4x+3+x
-4x=8
x=-2

5)
-4+2x-2x-4=3x-1+2x-5-7+3x
-8x=-5
x=5/8
Najlepsza Odpowiedź!
2010-02-23T16:33:56+01:00
2 (x+4) -5 (x+3) = 2
2x+8-5x-15=3
-3x-7=3/+7
-3x=10/: (-3)
x=3 1/3

-2 (x+3) +4 (2x+3) = -6
-2x-6+8x+12=-6
6x+6=-6/-6
6x=-12/:6
x=-2

(3-2x) + (3x+4)= - (3-2x) + ( 5x + 4 )
3-2x+3x+4=-3+2x+5x+4
7-x=1+7x/-7
-x=-6+7x/-7x
-8x=-6/: (-8)
x=6/8

- ( x+ 3) + (2x-1) = (1+ 4x) + (3 +x)
-x-3+2x-1=1+4x+3+x
x-4=4+5x/+4
x=8+5x/-5x
-4x=8/: (-4)
x=-2

- (4-2x) - (2x+4)= (3x-1) + ( 2x-5 -( 7-3x )
-4+2x-2x-4 = 3x-1 + (2x-5-7+3x)
-4+2x-2x-4 = 3x-1 + 2x-5-7+3x
-8=8x-13/-8x;+8
-8x=-5/: (-8)
x=5/8

Liczę na naj ;]]